Application of Ultrasonic to Enhance Sedimentation of Kaolin - M. Özer; F. Arslan; G. Önal (International Mineral Processing Congress, 2003)
"The use of ultrasonic in industrial processes has increased during the last few years. Ultrasonic vibrations are used in sieving, grinding, ore washing, cleaning, and flotation in mineral industry. There are also some attempts for the utilization of ultrasonic treatment in separation and removal of fine particles from gases and liquids. In Kalemaden A.S. (Turkey) four different types of clay mixtures (1. A mixture of clays from Balikesir-Düvertepe and Istanbul-Sile, 2. A mixture of clays from Ukrania and Balikesir-Düvertepe, 3. Sögüt-Kadikelimesi, 4. A mixture of clays from Sögüt and Istanbul-Sile) and kaolin from Balikesir-Düvertepe (Turkey) are concentrated before their use in ceramic production. Dewatering is the important step in those types of concentration plants. Sedimentation of concentrated clay has always been difficult and taken long times due to their nature and having small particle sizes. Flocculants can be used to enhance the sedimentation, but they are not preferred by the ceramic industry since they affect the quality of ceramic products. For this purpose, ultrasonic treatment is used in the sedimentation of clays mentioned above for solving the problems encountered related to the ceramic industry and promising results were obtained.Kaolin sample, subjected to this experimental study, from Balikesir-Düvertepe region of Turkey was brought from the plant as a pulp in containers and throughly mixed with a stirrer before sedimentation experiments. A two liter graduated cylinder and an ultrasonic bath (with 25 kHz frequency and 0.5 KW power) were utilized in the tests. Superfloc A-120 (1% concentration) was used as a flocculant. The settling distance was reported against the settling time during the experiments. Initial and final pulp densities were also determined. The effects of several parameters such as pulp density, flocculant addition, and ultrasonic treatment on the sedimentation of kaolin were investigated and the results are represented in terms of settling distance versus settling time."